Knockdown XIST alleviates LPS‐induced WI‐38 cell apoptosis and inflammation injury via targeting miR‐370‐3p/TLR4 in acute pneumonia - Zhang, Yena; Zhu, Yuyin; Gao, Guosheng; Zhou, Zhiming (Cell biochemistry and function, 2019)
Pneumonia is an inflammatory disease that occurs in the lungs associated with pathogens or other factors. It has been well established that long noncoding RNA X inactivate‐specific transcript (XIST) is involved in several cancers. The present study focused on the effect and detailed mechanism of XIST in lipopolysaccharide (LPS)‐induced injury in pneumonia. Here, XIST was silenced by transfection with XIST‐targeted siRNA, and then, mRNA expression, cell viability, apoptosis, and protein expression were, respectively, assessed by qRT‐PCR, CCK‐8, flow cytometry, and Western blotting. Luciferase reporter, RIP, and RNA pull‐down assays were used to detect the combination of miR‐370‐3p and XIST. Besides, the tested proinflammatory factors were analysed by qRT‐PCR and Western blot, and their productions were quantified by ELISA. The results showed that XIST expression was robustly increased in serum of patients with acute‐stage pneumonia and LPS‐induced WI‐38 human lung fibroblasts cells. Functional analyses demonstrated that knockdown of XIST remarkably alleviated LPS‐induced cell injury through increasing cell viability and inhibiting apoptosis and inflammatory cytokine levels. Mechanistically, XIST functioned as a competitive endogenous RNA (ceRNA) by effectively binding to miR‐370‐3p and then restoring TLR4 expression. More importantly, miR‐370‐3p inhibitor abolished the function of XIST knockdown on cell injury and JAK/STAT and NF‐κB pathways. Taken together, XIST may be involved in progression of cell inflammatory response, and XIST/miR‐370‐3p/TLR4 axis thus may shed light on the development of novel therapeutics to the treatment of acute stage of pneumonia. Significance of the study Our study demonstrated that XIST was highly expressed in patients with acute stage of pneumonia. Knockdown of XIST remarkably alleviated LPS‐induced cell injury through increasing cell viability and inhibiting apoptosis and inflammatory cytokine levels through regulating JAK/STAT and NF‐κB pathways.